2002
DOI: 10.1021/es010926m
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Mobility of Metal−EDTA Complexes in Groundwater:  The Influence of Contaminant Metals

Abstract: Reactive transport simulations were conducted to model chemical reactions between metal-EDTA (ethylenediaminetetraacetic acid) complexes during transport in a mildly acidic quartz-sand aquifer. Simulations were compared with the results of small-scale tracer tests wherein nickel-, zinc-, and calcium-EDTA complexes and free EDTA were injected into three distinct chemical zones of a plume of sewage-contaminated groundwater. One zone had a large mass of adsorbed, sewage-derived zinc; one zone had a large mass of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Numerous field studies have shown that complexation with EDTA may mobilize contaminant metal ions. EDTA may avoid the precipitation of heavy metals in solution or, on the contrary, cause a dissolution effect of heavy metals adsorbed in sediments 7,9,10 . Hence, the result is an enhanced mobilization of heavy metals.…”
Section: Ecotoxicological Risks Of Edtamentioning
confidence: 99%
“…Numerous field studies have shown that complexation with EDTA may mobilize contaminant metal ions. EDTA may avoid the precipitation of heavy metals in solution or, on the contrary, cause a dissolution effect of heavy metals adsorbed in sediments 7,9,10 . Hence, the result is an enhanced mobilization of heavy metals.…”
Section: Ecotoxicological Risks Of Edtamentioning
confidence: 99%
“…In real soils or sediments also dissolution of aluminum and manganese phases has to be considered (Jardine et al, 1993;Friedly et al, 2002), however, AlEDTA rapidly reacts with other phases and finally Fe(III)EDTA is formed. Drainage water from soil columns (calcareous soil, pH 7.6) to which EDTA had been added was found to contain high levels of dissolved iron, presumably in the form of Fe(III)EDTA (Madrid et al, 2003).…”
Section: Addition Of Edta: Metal and Metal-ligand Leaching Below The mentioning
confidence: 99%
“…Such a peculiarity of EDTA hinders the metal recovery in form of insoluble compounds, which is the common practice for treatment of spent solutions containing heavy metal ions. Resistant to chemical and biological degradation EDTA may also be capable to dissolve Fe 3+ , Al 3+ , Ca 2+ , Mg 2+ and heavy metals in soils and sediments, facilitating their movement in the hydrological cycle [1]. In a reciprocal manner the behavior of EDTA is itself influenced by the presence of metals.…”
Section: Introductionmentioning
confidence: 99%